Recuperação de cádmio de baterias níquel-cádmio via extração seletiva com tributilfosfato (TBP) Recovery of cadmium from nickel-cadmium batteries via selective extraction with tributylphosphate (TBP) - Ana Paula Mauro Gonçalves Barandas; Ivam Macedo Valverde Jr; Júlio Carlos Afonso; José Luiz Mantovano; José Waldemar Silva Dias da Cunha (Química Nova, 2007)
This work describes a recovery process of cadmium from spent nickel-cadmium batteries by a new hydrometallurgical route based on the selective extraction in hydrochloric acid medium with tributylphosphate (TBP), alone or dissolved in kerosene. The best results were obtained when TBP concentration was at least 75 vol%. Nickel extraction was negligible under these conditions. It was isolated after processing the rafinate through an anionic ion-exchange column. Final wastes generated are basically sodium chloride solutions, with no turbidity, color or heavy metals present in significant amounts.